STRATEGI PEMBERDAYAAN UMKM OLEH UNIT PELAKSANA TEKNIS PUSAT LAYANAN USAHA TERPADU KOPERASI USAHA MIKRO KECIL DAN MENENGAH (UPT PLUT KUMKM) PROVINSI RIAU - Apriyani "; Mayarni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Empowerment is an effort to prepare the community along with steps to strengthen community institutions so that they are able to realize progress, independence, and prosperity in a sustainable arrangement of justice. The concept of empowerment is not just to give assignments to the community but how to empower the community by giving direction and teaching so that people are accustomed to honing their abilities. This is what the Technical Service Unit of the Integrated Business Service Center for Micro, Small and Medium Enterprises (UPT PLUT KUMKM) of Riau Province wants to do. Empowerment is carried out by collaborating with accompanying consultants who have different capabilities in accordance with the needs of MSME actors. The purpose of this study is to formulate a small and medium micro business empowerment strategy and to find out what factors influence empowerment carried out by the Integrated Business Service Center for Micro, Small and Medium Enterprises (UPT PLUT KUMKM) in Riau Province. The research method used was descriptive qualitative which was then carried out strategy formulation using the SWOT analysis method. The results showed that the empowerment carried out was still not maximal and had not yet achieved the expected goals, the cause of which was a lack of socialization to the community about integrated business service centers that openly assisted the community in carrying out their business and human resources who were unable to compete with UMKM actors outside the area. Kata Kunci: Strategy, Community Empowerment